Faktor-faktor yang mempengaruhi struktur modal pada perusahaan perdagangan eceran yang terdaftar di BEI periode 2015-2020 - Angela, Michelle; Jumono, Sapto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the factors that affect the capital structure of retail trade sub-sector service companies listed on the Indonesia Stock Exchange for the 2015-2020 period by using purposive sampling as a sampling technique. This research method uses associative research using a quantitative method.. The sample used in this study was 15 companies with a total of 360 observations made for 6 years (quarters). The data analysis method used in this study is panel data regression which combines cross-section and time series data. The results of this study indicate that simultaneously the ROE, CR, AS, SIZE, GSTY, and DUMMY influence the capital structure (long-term debt to equity). The results in this study indicate that ROE, AS, SIZE, and DUMMY partially have a significant positive effect on capital structure (long-term debt to equity). Meanwhile, CR partially has a significant negative influence on capital structure (long-term debt to equity). And for the GSTY variable in this study, the results showed no effect on the capital structure (long-term debt to equity).